Investigating the mechanism of impact and differential effect of the Quality Premium scheme on antibiotic prescribing in England: a longitudinal study - Anwanyu, P; Pouwels, K; Walker, AS; Moore, M; Majeed, A; Hayhoe, BWJ; Tonkin-Crine, S; Borek, A; Hopkins, S; McLeod, M; Costelloe, C (Royal College of General Practitioners, 2020)
Background: In 2017, approximately 73% of antibiotics in England were prescribed from primary care practices. It has been estimated that 9%–23% of antibiotic prescriptions between 2013 and 2015 were inappropriate. Reducing antibiotic prescribing in primary care was included as one of the national priorities in a financial incentive scheme in 2015–2016.